FACTORS INFLUENCING UTILIZATION OF ELECTRONIC COMMUNITY HEALTH INFORMATION SYSTEM AMONG VILLAGE HEALTH TEAMS IN OGUR HEALTH CENTER IV, LIRA DISTRICT. A CROSS-SECTIONAL STUDY - Amito, Grace; Olinga, Michael Albert (Student’s Journal of Health Research Africa, 2025)
Background The Electronic Community Health Information System (eCHIS) is an integrated tool designed to assist Village Health Teams (VHTs) in making decisions and providing care support to their communities. This study aims to identify the factors influencing the utilization of eCHIS among VHTs at Ogur Health Center IV in Lira District. Methods The study employed a cross-sectional quantitative approach using simple random sampling, with a final sample size of 37 participants, and data analysis conducted using SPSS version 20.0 Results 20/37 (54.1%) were female, 13/37 (35.1%) were aged 36-45 years, and 21/37 (56.8%) had a secondary level education. 19/37 (51.4%) reported that they do not have access to a smartphone. 37/37 (100.0%), indicating that the availability of the internet in the community influences the utilization of eCHIS. 37/37 (100.0%), agreed that active community involvement is critical for the successful adoption of eCHIS. 5/37 (94.6%), indicated that users are more satisfied with eCHIS when they find the output information accessible, 29/37 (78.4%) reported that electronic equipment for this is available at the facility, 26/37 (70.3%), indicated that there is proper maintenance of ICT equipment in healthcare facilities, 29/37 (78.4%), agreed that leadership at the facility affects the utilization of eCHIS, while a minority of 8/37 (21.6%) disagreed. Conclusion Age, education, and smartphone access, Internet accessibility and community involvement were found to be critical for the successful adoption of eCHIS. Availability of electronic equipment, maintenance of ICT resources, and training support significantly influenced eCHIS usage. Recommendation The Ministry of Health, District Health Office, and Ogur Health Center IV recommend enhancing technological skills, expanding internet access, involving communities, and fostering leadership to improve eCHIS utilization through training, monitoring, and awareness campaigns.